2019
DOI: 10.3329/jbau.v17i4.44629
|View full text |Cite
|
Sign up to set email alerts
|

Combine Harvester: Impact on paddy production in Bangladesh

Abstract: Due to migration of agricultural labor in non-farm sectors and increasing climate vulnerability it is a great challenge to keep pace of food production for the exponential growth of population in Bangladesh. For following the traditional paddy harvesting methods, significant amount of field losses has been occurred in every year. The study was conducted to evaluate performance of combine harvester in comparison to manual harvesting of paddy and identify the impact on agricultural production system in Banglades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…The loss due to the use of combine harvesters is smaller than that caused by manual reaping and threshers in Egypt [53]. Similar results were found in Bangladesh [58], Myanmar [49], Dominican Republic [84], and Thailand [55]. However, some findings were contrary.…”
Section: Magnitude Of the Harvest Lossmentioning
confidence: 64%
See 3 more Smart Citations
“…The loss due to the use of combine harvesters is smaller than that caused by manual reaping and threshers in Egypt [53]. Similar results were found in Bangladesh [58], Myanmar [49], Dominican Republic [84], and Thailand [55]. However, some findings were contrary.…”
Section: Magnitude Of the Harvest Lossmentioning
confidence: 64%
“…If harvested too early, immature grains can make threshing difficult, resulting in more unthreshed loss [88]. Delayed harvesting may also cause substantial loss owing to shattering and extended exposure to natural incidents, such as attacks by birds and other pests [49,58,59], which is in line with farmers' perspectives [47]. Regression analyses in China confirmed that harvesting in time could reduce harvest loss [77].…”
Section: Causes Of Harvest Lossmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the condition of increasing productivity cannot be satisfied attributable to the shortage of manpower at that particular harvesting time. At the same time, since 1976, land availability for cultivation in Bangladesh has dropped by 68,760 ha•year −1 (0.73 percent) [1]. The alternative way to meet the grain requirement of the increasing population is to increase production with the help of mechanization.…”
Section: Introductionmentioning
confidence: 99%